Peer Group Support Decrease Depression Level In Menopause Woman - Ah. Yusuf; Ni Ketut Alit Armini; Deka Hardiyan (Jurnal Ners, 2008)
Introduction: Menopause woman has higher depression level than pre and postmenopause woman. Many woman who are getting menopause will feel lonely and don’t have any friends to talk, if this situation continue it can cause menopausal depression. Peer group support is one of group therapy which gives opportunity to menopause woman to get mutual support and help them to face the problem. This aimed of this study was to analyze the effect of peer group support in the menopause woman depression level.Methods: A quasy experimental pre-post test design was used in this study. There were 16 menopause women taken from Cepokomulyo Kepanjen. The independent variable was peer group support and the dependent variable was the depression level. Data were analyzed by Wilcoxon Signed Rank Test and Mann Whitney U Test with the significance level α<0.05.Results: Result showed that there was an effect of peer group support in the menopause woman depression level with significance level p=0.011 (treatment group) and p=0.23 (controlled group) and the result of Mann Whitney U Test showed that p=0.02.Conclusion: It can be concluded that peer group support can reduce the menopause woman depression level. It can be suggested to the institutional to practice peer group support to help menopause woman reduce their depression level.